Strategi komunikasi digital public relation dalam membangun reputasi bank syariah di era modern - hidayat, moh ahsanul (Maliki Interdisciplinary Journal, 2025)
The rise of digital technology has significantly transformed communication patterns within financial institutions, including Islamic banks. Amid the intense competition in the financial industry, the role of Public Relations (PR) is crucial in building and maintaining a positive image of Islamic banks. This paper analyzes the role and strategies of PR in strengthening public trust and improving the reputation of Islamic banks through digital media. Using a qualitative descriptive approach and literature review, this study finds that PR in Islamic banks serves not only as a promotional tool but also as a communication bridge that promotes trust, transparency, and Islamic values in the digital era..